PET in Multiple Sclerosis. (January 2015) - Niccolini, Flavia; Su, Paul; Politis, Marios
Abstract : Abstract: PET is a powerful in vivo functional imaging tool for investigating healthy and diseased brain. It provides noninvasive quantification of selected biological targets that could help build understanding of complex central nervous system disorders such as multiple sclerosis (MS). To date, in MS, PET could only offer complementary support to MRI studies because MRI has still a profound role in monitoring the clinical course of MS. However, recent developments in PET imaging offer the potential to assess the MS brain in vivo in a way that MRI is limited. PET in MS could be used for the investigation of underlying pathophysiology of neuroinflammation, neuronal dysfunction, and demyelination, and remyelination. Quantitative measures of molecular targets with PET could also have future uses in clinical trials of drug development. However, the use of PET is still limited because of the high costs of cyclotrons and radiochemical laboratories. Once these limitations are bypassed alongside advances in research, PET could help in the clinical practice of MS by providing a useful imaging tool for the accurate diagnosis, monitoring of clinical progression, and planning of treatment.